Radikalisme Islam dan Moderatisme Islam di Sekolah Menengah (Kontestasi Ideologi, Aktor dan Jejaring Sosial) - Thohiri, M. Kholid (Proceedings of Annual Conference for Muslim Scholars, 2019)
One form of the spread of the idea of ​​Islamic radicalism is through educational institutions of secondary school. This happened at SMA Negeri 1 Kedungwaru Tulungagung dan SMK Negeri 1 Bandung Tulungagung. The model of Islamic radicalism that developed in the two schools is the salafi-wahabi radical, takfiri radical, jihadist radical and political radical. The ideology of Islamic radicalism is spread through actors and social networks, namely non-Islamic education teachers, radical groups outside the school, and alumni They spread Islamic radicalism through the process of teaching and learning activities in the classroom and outside the classroom, religious activities in school mosques, alumni meetings and through social media. And the response and resistance of Islamic moderate groups in schools through restrictions, supervision and counter-ideological movements of Islamic radicalism with an understanding of moderate and tolerant Islam. Efforts to spread moderate understanding of Islam are carried out through the principal's policy, the role of PAI and non-PAI teachers, in various forms of activities and curriculum both in the classroom and outside the classroom, self-development activities and extra-curricular students who mainstream Islamic understanding in a moderate and multicultural perspective